(untitled) (PANGEEA, 2025)
Is there a communicative identity of the teacher? What communicative elements do we develop to succeed and establish an excellent didactic relationship with the students? I tried a few answers using a technique I called contextual communicational description. The exploratory study carried out confirms the fact that the communicative identity of the teacher is built and negotiated continuously in the relationship with the students.